Complete chloroplast genome sequence of historical olive (Olea europaea subsp. europaea) cultivar Mehras, in Jordan - Nizar Haddad; Hussein Migdadi; Mohammad Brake; Salam Ayoub; Wisam Obeidat; Yahya Abusini; Abeer Aburumman; Banan Al-Shagour; Eman Al-Anasweh; Monther Sadder (Mitochondrial DNA. Part B. Resources, 2021)
The complete chloroplast genome sequence of Olea europaea subsp. europaea cultivar Mehras was determined using high-throughput sequencing technology. Chloroplast genome was 155,897 bp in length, containing a pair of 25,742 bp inverted repeat (IR) regions, which were separated by large and small single-copy regions (LSC and SSC) of 86,622 and 17,791 bp, respectively. The chloroplast genome contained 130 genes (85 protein-coding, 37 tRNA, and eight rRNA). GC content was 37.8%. We performed phylogenetic analysis with other isolates. The analysis showed that O. e. subsp. europaea cultivar Mehras has an ancient common ancestor with cultivated olives in Italy, Spain, and Cyprus.